Unveiling the role of lipid metabolism in haemorrhagic disorders: genetic insights and therapeutic perspectives - Jiaqi Wei; Zhen Yang; Xiaojin Wu; Nana Zheng; Depei Wu (Thrombosis Journal)
Abstract Background Coagulation defects, including purpura and other haemorrhagic conditions, are a critical area of medical research because of their significant health effects worldwide. Understanding the metabolic basis of these conditions may improve therapeutic strategies. Methods A two-sample Mendelian randomization (MR) approach was employed to evaluate the causal relationships between the levels of 1,400 metabolites and coagulation defects. Colocalization analysis confirmed significant shared genetic influences. Pathway and protein‒protein interaction (PPI) analyses identified rate-limiting enzymes and drug targets. The impacts of lifestyle factors on metabolite levels were also explored through MR. Results MR analysis revealed four metabolites whose abundance was significantly associated with coagulation defects: docosapentaenoate n3 DPA 22:5n3 (DPA) (OR: 1.594, 95% CI: 1.263–2.011, P < 0.001), 1-palmitoyl-2-stearoyl-gpc (PSPC) (16:0/18:0) (OR: 1.294, 95% CI: 1.134–1.477, P < 0.001), 1-stearoyl-2-docosahexaenoyl-gpc (SDPC) (18:0/22:6) (OR: 1.232, 95% CI: 1.101–1.380, P < 0.001) and hydroxypalmitoyl sphingomyelin (HPSM) (d18:1/16:0 (OH)) (OR: 0.803, 95% CI: 0.719–0.896, P < 0.001). Colocalization analysis provided robust evidence for shared genetic loci. Pathway analysis highlighted the importance of lipid metabolism, identifying key enzymes such as FADS1, FADS2 and TCP1. PPI analysis revealed an interaction between TCP1 and plasminogen, indicating potential therapeutic synergy. Further analysis revealed that lifestyle factors, including dried fruit and oily fish intake, were linked to the abundance of metabolites associated with coagulation risk. Conclusions This study identifies specific metabolites and metabolic pathways involved in coagulation defects, proposes novel therapeutic targets and highlights the roles of dietary and lifestyle interventions in the management of these conditions. These findings pave the way for personalized strategies to manage coagulation-related conditions.